The evolution of pathogenic trypanosomes A evolução dos tripanossomas patogênicos - Jamie R. Stevens; Wendy C. Gibson (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1999)
In the absence of a fossil record, the evolution of protozoa has until recently largely remained a matter for speculation. However, advances in molecular methods and phylogenetic analysis are now allowing interpretation of the "history written in the genes". This review focuses on recent progress in reconstruction of trypanosome phylogeny based on molecular data from ribosomal RNA, the miniexon and protein-coding genes. Sufficient data have now been gathered to demonstrate unequivocally that trypanosomes are monophyletic; the phylogenetic trees derived can serve as a framework to reinterpret the biology, taxonomy and present day distribution of trypanosome species, providing insights into the coevolution of trypanosomes with their vertebrate hosts and vectors. Different methods of dating the divergence of trypanosome lineages give rise to radically different evolutionary scenarios and these are reviewed. In particular, the use of one such biogeographically based approach provides new insights into the coevolution of the pathogens, Trypanosoma brucei and Trypanosoma cruzi, with their human hosts and the history of the diseases with which they are associated. Os avanços recentes obtidos com os métodos moleculares e com a análise filogenética permitem atualmente interpretar a "história escrita nos genes", na ausência de um registro fóssil. A presente revisão se concentra em avanços recentes na reconstrução da filogenia dos tripanossomas, com base em dados moleculares obtidos do ARN ribossômico, do miniexon e dos genes codificadores de proteínas. Os dados já coletados demonstram inequivocamente que os tripanossomas são monofiléticos; as árvores filogenéticas derivadas podem servir como arcabouço para reinterpretar a biologia, taxonomia e distribuição atual das espécies de tripanossomas, elucidando sua co-evolução com os hospedeiros vertebrados e vetores. Diferentes métodos para datar a divergência das linhagens de tripanossomas dão hoje lugar a cenários evolucionários radicalmente distintos, que são revisados pelos autores. O uso de uma dessas abordagens biogeográficas fornece novas pistas sobre a co-evolução dos patógenos Trypanosoma brucei e Trypanosoma cruzi, com seus hospedeiros humanos e a história das doenças com as quais são associados.